The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3390/su12156258
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Customers as Sustained Competitive Advantages of Global Marketing Airline Alliances: A Hybrid Text Mining Approach

Abstract: Over the past several decades, the aviation industry has been reshaped, centering on global alliances, and these have grown exponentially. However, it is still not clear whether they are achieving sustained competitive advantages, and what are the specific competitive advantages of the three alliances (oneworld, SkyTeam, Star Alliance) arising on the customer side. This study aims to examine whether global alliance groups outperform the non-alliance group, how the three alliances differ regarding passengers’ p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The airline business has faced challenges in improving profitability and passenger service due to fluctuating oil costs and unexpected external environments, such as global epidemics. In order to achieve a sustainable competitive advantage, many airlines provide differentiated in-flight services to their passengers [1][2][3]. Although airlines publish their service manuals after a long period of research and efforts, they need to continuously improve and update their manuals due to the dynamic environment of the aviation industry [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The airline business has faced challenges in improving profitability and passenger service due to fluctuating oil costs and unexpected external environments, such as global epidemics. In order to achieve a sustainable competitive advantage, many airlines provide differentiated in-flight services to their passengers [1][2][3]. Although airlines publish their service manuals after a long period of research and efforts, they need to continuously improve and update their manuals due to the dynamic environment of the aviation industry [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…It is irrefutable that maximizing customer approach behaviors is an essential requisite of an airline company's successful management [10,11]. Preceding studies for the extant consumer behavior and marketing literature showed that providing a better quality physical environment to customers is one important way of eliciting positive post-consumption decisions/behaviors for the company [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…As moves to strengthen competitiveness, airlines have participated in global airline alliances. A global airline alliance is "any cooperative arrangement among two or more global airlines to realize their strategic goals and improve their competitive advantages" (Seo and Itoh, 2020).…”
mentioning
confidence: 99%